Trade, jobs and technological change: What to expect in the next five years? - Lucian Cernat (European Centre for International Political Economy (ECIPE), 2025)
This Policy Brief explores the intertwined effects of trade and technological change (notably robotics and AI) on employment, highlighting a growing divergence between the number of jobs supported by exports and the declining labour intensity of exports in recent years. The decline in labour intensity may be sharply accelerated by the rise of robotics and the automation of routine tasks, displacing workers in manufacturing and logistics while enhancing productivity. For many countries that have a strong dependence on the tradejobs nexus, the historically declining labour intensity of exports combined with the rapid adoption of robotics in key economic sectors, will mean that industries could now rely on fewer workers for their exporting activities. This dual shock suggests that, in the future, the number of jobs that depend on trade may decline. The convergence of these forces may lead to certain sectors or regions bearing the brunt of such potential labour disruptions. To address these challenges, supporting policies will be required to mitigate these adverse effects.
Keywords: 330; Außenhandel; Technischer Fortschritt; Erwerbstätigkeit; Arbeitsintensität; China; OECD-Staaten